Pengaruh Transfer Pemerintah Pusat terhadap Tax Effort Kabupaten/Kota di Provinsi Sumatera Barat - Army Devianti; Dewi Zaini Putri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
This study aims to estimate and explain the effect of government transfers on District/City Tax Effort in West Sumatra Province during the period 2012-2019. This type of research is quantitative research using secondary data with Panel Regression analysis model to analyze the effect of government transfers in the form of general allocation funds, profit sharing funds and special allocation funds on Tax Effort . The estimation results show that the General Allocation Fund, Revenue Sharing Fund and Special Allocation Fund have an effect on the growth of Regency/City Tax Effort in West Sumatra Province.